Religious Information on Identity Cards: A Turkish Debate - Esen, Selin (Journal of law and religion, 2008)
In 2006, the Turkish Grand National Assembly (TGNA) made a notable departure from historical precedent when it replaced the Population Register Law of 1972. The 1972 law, in Article 43, required that the national registry records on all households in Turkey contain the religion of all family members unless, under Article 46, an individual or family went to court to make a revision in these records. This was the legal basis of the inclusion of religious information on Turkish identity cards, issued in accordance with the information in family registers. Article 35 of The Population Services Law of 2006 now provides: "Requests about the religious information in household registers shall be approved, modified, left blank or deleted, in accordance with the written application of the concerned person."We shall argue, in this paper that Article 35 of the Population Services Law of 2006 is unconstitutional just like Article 43 of the Population Register Law of 1972 was, and that information about individuals' religions should be deleted from both the national register and individuals' identity (ID) cards. The inclusion of religious information in the identity cards of citizens or resident aliens, who apply for Turkish citizenship, violates the religious liberty in Turkey, particularly under a "neutrality" conception of that right. We shall review the jurisprudence of the Turkish Constitutional Court concerning ID cards in the light of the negative and positive aspects of religious liberty, focus on the different meanings of neutrality such as "formal neutrality," "substantive neutrality," "aim neutrality," "justification neutrality" and "consequences neutrality." Before we evaluate this practice under neutrality theory, however, it would be appropriate to begin with a historical narrative about the origin of religious notations on Turkish identity cards, and explain the content and the meaning of the new law.